Quantifying the P–T–t conditions of north–south Lhasa terrane accretion: new insight into the pre‐Himalayan architecture of the Tibetan plateau. (19th November 2014) - Weller, O. M.; St‐Onge, M. R.; Searle, M. P.; Waters, D. J.; Rayner, N.; Chen, S.; Chung, S.‐L.; Palin, R. M.
Abstract An integrated field, petrological and geochronological study of the Basong Tso region of south‐eastern Tibet has constrained the timing and P–T conditions of north–south Lhasa terrane accretion and provides new insight into the tectonothermal evolution of the Tibetan plateau. Two distinct high‐grade metamorphic belts are recognized in the region: a southern belt (the Basong Tso complex) that consists of sheared schist and orthogneiss; and a northern belt (the Zhala complex) that comprises paragneiss and granite. Combined pseudosection modelling and U–Pb geochronology of monazite and zircon indicates that the Basong Tso complex records peak metamorphic conditions of 9 ± 0.5 kbar and 690 ± 25 °C at c. 204–201 Ma, whereas the Zhala complex experienced peak metamorphic conditions of 5.0 ± 1.0 kbar and 740 ± 40 °C at c. 198–192 Ma. Microstructural analysis suggests that the two belts share a common early prograde history, after which the Basong Tso complex attained peak conditions following rapid burial, and the Zhala complex approached peak conditions along an isobaric path. Overall it is inferred that the Basong Tso and Zhala complexes represent the lower and upper structural levels of an evolving orogen that underwent Barrovian‐type metamorphism following collision (M1), followed by Buchan‐style overprinting at higher structural levels due to heat advection by syn‐tectonic granites (M2). Mylonitization (sensu lato) of the Basong Tso complex and juxtaposition of the two units occurred after attainment of peak conditions. The dominance of Mesozoic regional metamorphism across most of the Tibetan plateau indicates that Cenozoic crustal thickening processes, where present, are only manifested at depth.